UJI TOKSISITAS SUBLETAL EFLUEN INDUSTRI MENGGUNAKAN IKAN NILA (Oreochromis niloticus) SEBAGAI ALAT PEMANTAUAN BIOLOGIS - Atiek Moesriati (Purifikasi, 2004)
The gills of nila fish which was exposed to the effluent of copper smelter and surfactant plants showed 100% hyperplasia. Whereas the effluent of paper plant caused 79,13% hyperplasia on lamella branchialis. The effluent concentration of copper smelter plant which gave significant influence of respiration rate was 40% volume with TDS, TSS, Fe, Zn, Cd, Pb, F concentrations of 1.590 mg/l, 27 mg/l, 0,39 mg/l, 0,116 mg/l, 0,12 mg/l, 0,048 mg/l and 0,044 mg/l respectively. Surfactant plant effluent that caused significant influence of respiration rate was 60% volume with BOD, COD, TSS, MBAS concentrations of 2,4 mg/l, 17,76 mg/l, 31,2 mg/l, and 0,6 mg/l respectively.